Needs and potential use of augmented reality in teaching and learning computer architecture and organization course: a pilot study / Anis Salwani Abu Bakar, Hasliza A Rahim & Noraini Desa - Abu Bakar, Anis Salwani; A Rahim, Hasliza; Desa, Noraini (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Augmented reality generally defined as an enhanced version of the real physical world accomplished through the use of visual elements, sound, or other sensory stimulation delivered through various platforms of technology application. In the Electrical Engineering Department of Politeknik Sultan Haji Ahmad Shah, the Computer Architecture and Organization Course is still being delivered to students via conventional methods of interactive lectures and discussion in the classroom. Despite the fact that blended learning approach has been implied, students’ understanding of the course is still at a low level based on their achievement in continuous assessment and final examination. Considering that this course is one of the difficult courses offered to students majoring in Diploma In Electronic Engineering (Technology Computer), the teaching and learning process always ends up with merely teacher centred learning rather than student centred learning. Hence this study aims to identify the needs and potential constructs or topics that are suitable to adopt augmented reality (AR) innovation in teaching and learning of Computer Architecture and Organization Course in order to help in increasing the students’ understanding and achievement. Further findings reveal that students and lecturers showed very high perception of the necessity of using AR in Computer Architecture and Organization Course teaching and learning processes. The adoption of AR is expected to become an effective teaching innovation method for lecturers and consequently assist the students to improve their understanding and achievement in the course. Further study is also expected in reviewing the effectiveness and implementation of AR innovation model that will be developed later on.